Effect of gabapentin on sexual function in vulvodynia: a randomized, placebo-controlled trial - Bachmann, Gloria A.; Brown, Candace S.; Phillips, Nancy A.; Rawlinson, Leslie A.; Yu, Xinhua; Wood, Ronald; Foster, David C.; Dawicki, Diane; Bonham, Adrienne; Dworkin, Robert; Balabathula, Pavan; Bachour, Candi; et al. (American journal of obstetrics and gynecology, 2019)
Sexual dysfunction is common in women with vulvodynia. The purpose of this study was (1) to evaluate whether extended-release gabapentin is more effective than placebo in improving sexual function in women with provoked vulvodynia and whether there is a relationship between treatment outcome and pelvic pain muscle severity that is evaluated by palpation with standardized applied pressure and (2) to evaluate whether sexual function in women with provoked vulvodynia would approach that of control subjects who report no vulvar pain either before or after treatment. As a secondary outcome in a multicenter double-blind, randomized crossover trial, sexual function that was measured by the Female Sexual Function Index was evaluated with gabapentin (1200–3000 mg/d) compared with placebo. Pain-free control subjects, matched by age and race, also completed Female Sexual Function Index for comparison. From August 2012 to January 2016, 230 women were screened at 3 academic institutions, and 89 women were assigned randomly to treatment. Gabapentin was more effective than placebo in improving overall sexual function (adjusted mean difference, 1.3; 95% confidence interval, 0.4–2.2; P=.008), which included desire (mean difference, 0.2; 95% confidence interval, 0.0–3.3; P=.04), arousal (mean difference, 0.3; 95% confidence interval, 0.1–0.5; P=.004), and satisfaction (mean difference, 0.3; 95% confidence interval, 0.04–0.5; P=.02); however, sexual function remained significantly lower than in 56 matched vulvodynia pain-free control subjects. There was a moderate treatment effect among participants with baseline pelvic muscle pain severity scores above the median on the full Female Sexual Function Index scale (mean difference, 1.6; 95% confidence interval, 0.3–2.8; P=.02) and arousal (mean difference, 0.3; 95% confidence interval, 0.1–0.6; P=.01) and pain domains (mean difference, 0.4; 95% confidence interval, 0.02–0.9; P=.04). Gabapentin improved sexual function in this group of women with provoked vulvodynia, although overall sexual function remained lower than women without the disorder. The most statistically significant increase was in the arousal domain of the Female Sexual Function Index that suggested a central mechanism of response. Women with median algometer pain scores >5 improved sexual function overall, but the improvement was more frequent than the pain domain. We hypothesize that gabapentin may be effective as a pharmacologic treatment for those women with provoked vulvodynia and increased pelvic muscle pain on examination.